Isolation of Human Platelets (Thrombocytes) - John Graham (The Scientific World Journal)
Platelets from human blood can be isolated in high yield by centrifugation of whole blood over an iodixanol density barrier of 1.063 g/ml. The separation from all of the blood cells (which form a pellet) is based on the slower sedimentation velocity of the smaller platelets.